Photoreceptor ablation following ATP induced injury triggers Müller glia driven regeneration in zebrafish. (June 2021) - Brandli, Alice; Dudczig, Stefanie; Currie, Peter D.; Jusuf, Patricia R.
Abstract: Retinal regeneration research offers hope to people affected by visual impairment due to disease and injury. Ongoing research has explored many avenues towards retinal regeneration, including those that utilizes implantation of devices, cells or targeted viral-mediated gene therapy. These results have so far been limited, as gene therapy only has applications for rare single-gene mutations and implantations are invasive and in the case of cell transplantation donor cells often fail to integrate with adult neurons. An alternative mode of retinal regeneration utilizes a stem cell population unique to vertebrate retina – Müller glia (MG). Endogenous MG can readily regenerate lost neurons spontaneously in zebrafish and to a very limited extent in mammalian retina. The use of adenosine triphosphate (ATP) has been shown to induce retinal degeneration and activation of the MG in mammals, but whether this is conserved to other vertebrate species including those with higher regenerative capacity remains unknown. In our study, we injected a single dose of ATP intravitreal in zebrafish to characterize the cell death and MG induced regeneration. We used TUNEL labelling on retinal sections to show that ATP caused localised death of photoreceptors and ganglion cells within 24 h. Histology of GFP-transgenic zebrafish and BrdU injected fish demonstrated that MG proliferation peaked at days 3 and 4 post-ATP injection. Using BrdU labelling and photoreceptor markers (Zpr1) we observed regeneration of lost rod photoreceptors at day 14. This study has been undertaken to allow for comparative studies between mammals and zebrafish that use the same specific induction method of injury, i.e. ATP induced injury to allow for direct comparison of across species to narrow down resulting differences that might reflect the differing regenerative capacity. The ultimate aim of this work is to recapitulate pro-neurogenesis Müller glia signaling in mammals to produce new neurons that integrate with the existing retinal circuit to restore vision. Highlights: Intravitreal injection of adenosine triphosphate (ATP) caused photoreceptor and ganglion cell death in fish. ATP induced Muller glia proliferated three and four days after injection. Regeneration of rod photoreceptors observed 14 days after injection.